Evaluation of ethanol-based extraction conditions of sorghum bran bioactive compounds with downstream anti-proliferative properties in human cancer cells. Issue 5 (May 2019) - Cox, Sarah; Noronha, Leela; Herald, Thomas; Bean, Scott; Lee, Seong-Ho; Perumal, Ramasamy; Wang, Weiqun; Smolensky, Dmitriy
Abstract: Certain foods such as turmeric and green tea have been extensively studied for anticancer properties, while high polyphenol sorghum has not received the same attention. Some bioactive compounds in Sorghum bicolor with anticancer activity have been identified, indicating the further need for research and screening methods of high polyphenol sorghum varieties. This study was aimed at improving the extraction of sorghum bioactive compounds by using food-grade solvents using ethanol and citric acid. We used three sorghum varieties and green tea (GT) as a control. The extraction methods were screened for anti-proliferative properties in HepG2 and HCT-15 cancer cell lines, using a cell viability assay. Extraction conditions were improved for anti-proliferative compounds from a high-phenolic sorghum variety (HP), sumac sorghum (CS), and GT. HP was more effective at inhibiting cell viability than CB, CS, and GT. The results demonstrate an efficient method for extracting sorghum bioactive compounds for future anticancer research using food approved ingredients.